Conocimientos sobre tamizaje neonatal en madres que acuden al Centro de Salud N° 3, Loja - Peña Andrade, Andrea Yazmín (2019)
The Neonatal Metabolic Screening allows the early detection and management of metabolic errors of diseases such as: Congenital Hypothyroidism, Phenylketonuria, Galactosemia and Congenital Adrenal Hyperplasia. It is usually done on the fourth day of life of the newborn. The opportune diagnosis allows to prevent intellectual disability and early death in newborns. From the year 2011 that began to perform this test in Ecuador, under the biopsychosocial study that determined that 2.34 x 100,000 inhabitants have disabilities in the country, have been discovered cases of adrenal hyperplasia, hypothyroidism, galactosemia and phenylketonuria, for In the present investigation, the general objective was to determine the level of knowledge about Neonatal Screening in mothers who come to the Centro de Salud N°3 of the city of Loja. As a methodological design, a descriptive study was conducted involving 110 mothers who attended this health house, in the period between October 2018 and March 2019, the technique of data collection was the interview, the instrument to collect the information was represented by a questionnaire that consisted of closed questions, which correspond to the objectives of the investigation. This study allowed us to conclude that the majority of mothers who come to the Centro de Salud N°3, do not have the adequate level of knowledge about Neonatal Screening since the following results were obtained: 44% have low knowledge, 41% have a medium knowledge and 15% a high knowledge. KEYWORDS: neonatal metabolic screening, knowledge, mothers, metabolic diseases, intellectual disability